eBroker: An agent-based query routing system for distributed E-commerce databases - BHOWMICK, Yong (Institutional Knowledge at Singapore Management University, 2000)
With the rapid increase in the number of E-commerce web sites, Internet users are now able to purchase items from the web. Nevertheless, the large number of E-commerce web sites also brings about the problem of identifying sites that sell the desired products wanted by a potential buyer. To avoid broadcasting the same queries on products to large set of databases maintained at different E-commerce web sites, buyers can rely on a query routing system that matches the queries with the E-commerce database content. Much of the previous work in query routing has focused on databases that are document collections and queries that involve text attributes only. In this paper, we propose a new database selection technique designed for distributed E-commerce databases. The technique deals with queries that involve attributes of different data types. We have incorporated the proposed technique into an agent-based query routing system known as eBroker. The performance of e-Broker for the E-commerce databases of 5 online CD stores will be reported.